A Valence Control Method Based on a Pt-Aided Hydrogen Peroxide Treatment for Yielding Tetravalent Neptunium and Plutonium in Nitric Acid Solutions - 서무열; 이명호; 손세철; 지광용; 이창헌; 한선호; Byoung Chul Song (Bulletin of the Korean Chemical Society, 2008)
KCI Citation Count: 1